Fatty Acid Profile of Pacific Oyster, Crassostrea gigas, Fed Different Ratios of Dietary Seaweed and Microalgae during Broodstock Conditioning. Issue 9 (17th July 2019) - Rato, Ana; Pereira, Luís F.; Joaquim, Sandra; Gomes, Romina; Afonso, Cláudia; Cardoso, Carlos; Machado, Jorge; Gonçalves, José F. M.; Vaz‐Pires, Paulo; Magnoni, Leonardo J.; Matias, Ana M.; Matias, Domitília; et al.
Abstract: The fatty acid (FA) profile of oysters generally reflects the dietary FA composition. Moreover, incorporation of FA into tissues is modulated by various metabolic factors, and final composition will depend upon the dietary sources, cumulative intake, and oysters' development stage. Thus, the aim of this study was to assess the impact of dietary incorporation of seaweed (SW) Ulva rigida, in replacement of traditional microalgae diet, on the FA composition of Pacific oysters Crassostrea gigas, during broodstock conditioning. The dietary conditioning consisted of direct replacement of microalgae (33% Tisochrysis lutea, 50.25% Skeletonema costatum, and 16.75% Chaetoceros calcitrans ) by SW at four different substitution levels (0%, 25%, 50%, and 100% diet). The dietary docosahexaenoic acid (DHA) (22:6n‐3) and eicosapentaenoic acid (EPA) (20:5n‐3) contents showed a positive correlation with the dietary microalgae level. During the trial, oysters fed with higher percentages of microalgae revealed a depletion of DHA and accumulation of EPA. The 100% SW caused a significant reduction in oxygen consumption and, consequently, in the standard metabolic rate. Based on these results, a partial substitution of up to 25% of dietary microalgae seems to be a suitable alternative, because it elicited similar results to the commercial 100% microalgae diet.